2014
DOI: 10.1097/rct.0000000000000082
|View full text |Cite
|
Sign up to set email alerts
|

Transient Reduction of Spleen Density in Acute Pancreatitis

Abstract: A healthy spleen has density stable on computed tomographic (CT) scan; in some patients, spleen infarction can be associated with acute pancreatitis. Here, we report 2 patients with acute pancreatitis associated with transient reduction of spleen density that were confirmed in our hospital. The clinical data of the 2 patients were retrospectively analyzed, and the relevant literature was reviewed. Acute pancreatitis with transient reduction of splenic density has certain characteristics in clinical and radiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…Because DROSD in AP might be related to high blood lipid levels, we analysed the correlations of TC and TG with spleen density by logistic regression [ 10 ]. As shown in Figure 6 a and b, TC and TG did not differ between the control and reduction groups of patients with AP (4.69 ± 1.95 compared with 5.26 ± 2.88, β = −0.096, P =0.32, P >0.05; 3.82 ± 3.15 comapred with 4.12 ± 4.22, β = −0.019, P =0.723, P >0.05).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Because DROSD in AP might be related to high blood lipid levels, we analysed the correlations of TC and TG with spleen density by logistic regression [ 10 ]. As shown in Figure 6 a and b, TC and TG did not differ between the control and reduction groups of patients with AP (4.69 ± 1.95 compared with 5.26 ± 2.88, β = −0.096, P =0.32, P >0.05; 3.82 ± 3.15 comapred with 4.12 ± 4.22, β = −0.019, P =0.723, P >0.05).…”
Section: Resultsmentioning
confidence: 99%
“…The spleen is an abdominal parenchymal organ of the human body, and a healthy spleen has stable density on CT scans (the CT value is 40–55 HU) [ 10 , 26 ]. However, we recently observed that AP could be associated with DROSD in some patients clinically ( Figure 2 b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, it has been mentioned that the density of the spleen is reduced by the high lipid concentration during hyperlipidemic acute pancreatitis. [ 24 ] However, the plasma lipid of the patient in Case A was normal. The integrated therapeutic strategy of HP includes pain control, prevention of recurrence, treatment of exocrine (maldigestion) and endocrine (diabetes) dysfunction, management of complications (pseudocysts, etc), and early detection of pancreatic ductal adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%